Reinterpreting the Exegesis of Verses 82 and 83 of Sūrah an-Nisāʾ Through a Mystical Studying - Mohsen Nurai; Tahere Naji Sadreh (آموزه‌های قرآنی, 2024)
A mystical interpretation of Qurʾānic verses, grounded in rigorous exegetical principles and informed by the proper methodology of tadabbur (Arabic: التدبر, lit: deep contemplation), is not only possible but also essential, as it facilitates the discovery and extraction of novel meanings from the Qurʾān. This approach has been realized in numerous mystical exegeses. However, commentators in this tradition often fail to elucidate the methodological foundations underlying their novel understandings of the verses. Consequently, they are frequently accused of inconsistencies in tafsīr (Arabic: تفسیر) and taʾwīl (Arabic:تأویل), an overreliance on associative meanings, subjective interpretations, and methodological arbitrariness. Yet, a clear articulation of their reasoning could enhance the credibility of their interpretations. Verses 82 and 83 of Sūrah an-Nisāʾ (04), when interpreted through a conventional exoteric perspective, pertain to governance-related discussions. However, a meticulous examination of their internal and external textual context-especially in light of the preceding verse-reveals their potential to convey deeper meanings. Adopting a descriptive-analytical approach, this article seeks to elucidate the evidentiary basis and contextual indicators that substantiate a mystical interpretation of these verses, thereby unveiling their semantic depth. From this perspective, these verses explicitly affirm the esoteric knowledge of those endowed with the capacity for istinbāṭ (Arabic: إستنباط, lit: deductive reasoning) concerning the inner dimensions of the Qurʾān. They further underscore the necessity of presenting such insights to the infallible (maʿṣūm, Arabic: معصوم) and affirm the absence of contradiction among the genuine spiritual discoveries of mystics. Ultimately, these verses may allude to one of the highest stations in the mystical path, namely kitmān (Arabic: کتمان, lit: concealment of esoteric knowledge).